القدرات الإبداعية لدى الطلبة الموهوبين وفقا لمقايس أبراهام تمبل في مدارس ومراكز الموهوبين في محافظة البلقاء في الأردن - العواملة، حابس سليمان (جامعة المنصورة - كلية التربية النوعية, 2012)
هدفت هذه الدراسة إلى الكشف عن القدرات الإبداعية لدى الطلبة الموهوبين في مدارس الملك عبد الله الثاني للتميز والمراكز الريادية في مدينة السلط كما هدفت إلى استقصاء الفروق التي تعزى لمتغيرات الدراسة ( الجنس، الصف، المعدل التراكمي)، على مستويات القدرات الإبداعية لدى الطلبة الموهوبين. \ تكونت عينة الدراسة من (100) طالباً وطالبة من الصف السابع والتاسع والعاشر منهم (50) ذكور و (50) إناث من الصفوف المذكورة في مدرسة الملك عبد الله الثاني للتميز والمراكز الريادي في مدينة السلط للعام الدراسي 2010-2011. \ \ تم استخدام مقياس ابراهام- تمبل المعرب للبنية المصرية من قبل مجدى عبد الكريم حبيب وتم استخدام المتوسطات الحسابية والانحرافات المعيارية واختبار T-test لفحص أسئلة الدراسة وتم استخدام تحليل التباين الأحادي one way-ANOVA ولمعرفة المقارنات البعدية تم استخدام اختبار شيفيه، وقد توصلت نتائج الدراسة إلى أن بُعد الطلاقة جاء بمستوى متوسط في حين جاء بعدي الأصالة والمرونة بمستوى متدني، كذلك توصلت إلى وجود فروق ذات دلالة بين أداء الطلبة في جميع أبعاد الدراسة يعزى لمتغير الجنس، وجاء لصالح الإناث. \ \ كذلك بينت نتائج الدراسة إلى وجود فروق ذات دلالة لمتوسط أداء العينة على أبعاد المقياس لمصلحة الصف العاشر على حساب الصف السابع والتاسع كذلك أشارت إلى وجود الفروق ذات الدلالة لمصلحة المعدل التراكمي للطالب (85 أو أعلى) على حساب المعدل التراكمي (69من دون). This study aimed to uncover the creative abilities of gifted students in the schools of king Abdullah II Award for Excellence centers and leadership it, the city of Salt also aimed to explore the differences attributable to the variables of the study (sex, grade, GPA), the levels of the creative capabilities of gifted students. \ \ The study sample consisted of (100) students from the seventh grade, ninth and tenth of them (50) males and (50) female school grades mentioned in the King Abdullah II Award for Excellence and the leading centers in the city of Salt for the academic year 2010-2011. \ \ Used measure of Abraham-Temple expressed the structure of the Egyptian by magdi Abdel Karim Habib, was used averages, standard deviations, test T-test to examine the questions of the study was the use of analysis of variance single one way-ANOVA and to find out comparisons a posteriori test was used Scheaffe, The Results of the study After that the average level of fluency was when he came in me originality and flexibility, a low level, as well as the findings to the existence of significant differences between the performance of students in all dimensions of the study due to the variable of sex, and was in favor of females. \ \ They also showed the results of the study to the existence of significant differences to the average performance of the sample on the dimensions of the scale in favor of the tenth grade at the expense of the seventh grade and ninth also pointed to the existence of differences of significance for the benefit accrual rate for the student (85 or higher) at the expense of average cumulative (69 without).
Keywords: مدارس الموهوبين -- القدرات الإبداعية -- التفكير الإبداعي -- مهارات التفكير -- الطلاب الموهوبون -- مقياس أبراهام تمبل -- مراكز الموهوبين -- البلقاء -- الأردن -- الفروق الفردية -- التحليل النفسي -- التحصيل الدارسي -- علم النفس التربوي -- رعاية الموهوبين